The Role of Internal Audit in the Implementation of Good University Governance to Improve Financial Management Accountability (Case Study at PTN-BH, Universitas Pendidikan Indonesia) - Nursyifa Rahma Kamila; Dadang Enjat Munajat (Green Publisher Indonesia, 2025)
This study aims to analyze the role of internal audit in the implementation of Good University Governance (GUG) at the University of Education Indonesia (UPI), which has the status of a Legal Entity State University (PTN-BH). The main focus is on how the role improves financial management accountability within the university environment. Internal audit has an important role as an internal control mechanism to ensure transparency and accountability in financial statements, thereby supporting the achievement of Good University Governance (GUG) principles, such as transparency, accountability, responsibility, independence, and fairness. The study also highlights various challenges in the implementation of Good University Governance (GUG) at UPI, including limited internal auditor resources. The results of the study show that the existence of an effective internal audit is able to increase public trust through reliable financial reporting. Therefore, this study provides strategic recommendations to increase the capacity and professionalism of internal auditors to support better university governance.